Factors predicting the occurrence of syringomyelia in patients with Chiari I malformations - Peettakkandy, Vijayan; Rajagopalawarrier, Bijukrishnan; Kuniyil, Sreenath; Thankaraj, Jithin Veliyath (International Journal of Research in Medical Sciences, 2019)
Background: Chiari I malformations are defined as the downward herniation of cerebellar tonsils more than 5 mm through the foramen magnum. Syringomyelia is a common association of Chiari I malformation. Methods: This purpose of this study was to determine the various factors predicting the occurrence of syringomyelia in patients with Chiari I malformations. This retrospective study was conducted in Government medical college, Thrissur, Kerala, India. 27 patients admitted with diagnosis of symptomatic Chiari I malformations during the period of January 2015 to January 2019 were selected for the study. Results: The mean age was 22.8 years and syringomyelia was more common in patients older than 10 years (p value0.005). Females were 17(63%) and males were 10(37%) but there no difference in occurrence of syringomyelia among both sexes(p value is 0.16). Syringomyelia was present in 17(63%) cases. Association between various factors and syringomyelia measured by calculating P value which was 0.005 for age >10 years, 0.16 for sex, 0.093 for duration of symptoms >12 months, 0.05 for tonsillar descend >10mm and 0.097 for hypertension. The p value for the association of duration of symptoms >12months and extend of tonsillar descend is 0.001 Mean duration of symptoms (onset of first symptom to the time of presentation) was 16.3 months and syringomyelia was more common in patients with duration of symptoms more than 12 months but this difference was statistically not significant (p value 0.093). Mean tonsillar descend from the level of foramen magnum was 11.3 mms and syringomyelia was more common in patients with tonsillar herniation more than 10mm (p value 0.05). There is a statistically significant relationship between duration of symptoms more than 12 months and tonsillar descend more than 10mm(p value 0.001).There is no significant association between hypertension and occurrence of syringomyelia in patients with Chiari I malformation. Conclusions: Incidence of Chiari I Malformations is more among adults and it is slightly higher in females. Syringomyelia is a common association of Chiari I Malformations. The occurrence of syringomyelia in patients with Chiari I Malformations associated with increasing age of patients and extend of tonsillar herniation. There is no statistically significant association between syringomyelia and duration of symptoms or hypertension.